Monte carlo investigation of ferromagnetic properties under compressive stress - Laosiritaworn Y. (2014)
In this work, we used Monte Carlo simulations to model the three-dimensional ferromagnetic Ising spins under the influence of uniaxial and hydrostatic compressive mechanical stresses. The study was performed with a cluster-flip algorithm to investigate how the magnetic properties including critical behaviors depend on temperatures and the applied mechanical stresses. From the results, the magnetic profiles as a function of temperature were obtained and it was found that the applied stresses lowered the magnetic phase transition point. However, the critical exponents to the relevant observables did not significantly change. This suggests universality behavior in magnetic systems under loading environment.